2014
DOI: 10.1074/mcp.m113.034215
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Proteomic and Metabolic Adaptations Associated with Alterations of Seed Yield and Quality in Sulfur-limited Brassica napus L

Abstract: In Brassica napus, seed yield and quality are related to sulfate availability, but the seed metabolic changes in response to sulfate limitation remain largely unknown. To address this question, proteomics and biochemical studies were carried out on mature seeds obtained from plants grown under low sulfate applied at the bolting (LS32), early flowering (LS53), or start of pod filling (LS70) stage. The protein quality of all low-sulfate seeds was reduced and associated with a reduction of S-rich seed storage pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 45 publications
4
54
0
Order By: Relevance
“…Additionally, our study shows that cropping (monocrops or mixtures) or S application conditions had effect on either the seed quality components (protein, oil and glucosinolate concentrations, and oil composition) or on the ω‐6 : ω‐3 ratio (Tab. ) of rapeseed seeds, which remained close to 2, a value considered as good for rapeseed oil quality ( D'Hooghe et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, our study shows that cropping (monocrops or mixtures) or S application conditions had effect on either the seed quality components (protein, oil and glucosinolate concentrations, and oil composition) or on the ω‐6 : ω‐3 ratio (Tab. ) of rapeseed seeds, which remained close to 2, a value considered as good for rapeseed oil quality ( D'Hooghe et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition to these strong N requirements, winter oilseed rape also requires high inputs of sulfur (S) fertilizer (McGrath and Zhao, 1996;Scherer, 2001). Rapeseed is highly sensitive to S mineral limitation, which induces a reduction in yield and the quality of harvest products through modifications of lipids and protein composition of seeds (McGrath and Zhao, 1996;Malhi et al, 2007;Scherer, 2001;D'Hooghe et al, 2014). In addition, Dubousset et al (2010) have shown that decreased S availability reduces the N use efficiency of oilseed rape.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the effects of S deficiency on the Mo accumulation previously described, it could be hypothesized that the leaf [Mo]:[S] ratio might serve as an indicator of S nutrition to predict S deficiency. For S-demanding crops such as oilseed rape, S deficiency provokes multiple plant physiological changes leading to losses in yield and seed quality through modified lipid and protein composition of seeds [30, 31, 32, 33, 34]. It has already been suggested that the analysis of plants rather than soil via total S, SO 4 2- or N:S, malate:sulfate or ([Cl - ]+[NO 3 - ]+[PO 4 3- ]):[SO 4 2- ] ratios could be used to detect plant S requirements (for review see [35, 36] but these parameters are affected by growth stage and growth rates or need laboratory analyses, making them unreliable as diagnostic indicators [35, 37].…”
Section: Introductionmentioning
confidence: 99%
“…S deprivation in oilseed rape leads to reduced seed yields and oil quality (Janzen and Bettany, 1984 ; Scherer, 2001 ). Recent work based on proteomics approaches in mature seeds obtained from winter oilseed rape plants grown under low sulfate applied at the bolting, early flowering or start of pod filling stages (D'Hooghe et al, 2014 ) have revealed that the protein quality of seeds was reduced depending on the severity of S limitation and was associated with a reduction in S-rich seed storage protein accumulation (such as Cruciferin Cru4) which favored S-poor seed storage protein (such as Cruciferin BnC1). Nevertheless, our knowledge about the stages of development the more sensitive to S limitation or the physiological processes that are involved in S management by oilseed rape subjected to sulfate restriction remains largely unclear (Dubousset et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%